Digital Storytelling dan Nilai Hijau: Membangun Niat Beli terhadap Tas Belanja Ramah Lingkungan - Yuni Adinda Putri; Yolanda Veybitha; Yuni Rachmawati; Muhammad Nur Muttaqin; Widya Anisa Pratiwi; Aisyah Regita (Universitas Muhammadiyah Bengkulu, 2026)
This study explores how Digital Storytelling (DS) and Green Value Perception (GVP) influence consumers’ Purchase Intention (PI) toward recycled plastic shopping bags, with Customer Engagement (CE) acting as a mediating variable. Guided by the Theory of Planned Behavior (TPB), Narrative Transportation Theory, and Customer Engagement Theory, the research investigates how emotional stories and perceptions of environmental value encourage sustainable purchasing decisions. Data were obtained from 360 respondents in Palembang City, Indonesia, through a structured online survey, and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that both DS and GVP have significant positive effects on CE and PI, while CE partially mediates these relationships. These findings suggest that when consumers are emotionally drawn into authentic digital narratives and perceive clear ecological benefits, they are more likely to act on sustainable intentions. This study extends the growing body of sustainability marketing research by offering an integrative framework that connects narrative-based communication, perceived green value, and consumer engagement—providing insights especially relevant for developing markets seeking to foster environmentally responsible behavior.